Asphyxia and Neonatal Respiratory Distress Syndrome Are Independent Predictors of the Non-response to Inhaled Nitric Oxide in the Newborns With PPHN - Yuwei Zhao; Lei Liang; Guanghui Liu; Hong Zheng; Liying Dai; Yan Wang; Lei Wang; Weiting Sheng (Frontiers Media S.A., 2021)
Aim: Not all the neonates respond with improvement in oxygenation following inhaled nitric oxide treatment (iNO) treatment. The aim of this study was to assess the independent risk factors associated with non-response to iNO during the 2 weeks of postnatal treatment in neonates diagnosed with persistent pulmonary hypertension (PPHN).Materials and Methods: This retrospective cohort study included all newborns with PPHN who received iNO treatment for more than 24 h. Demographic, obstetric, perinatal data and clinical complications were extracted from the hospitalization records. Subjects were divided into two groups according to their response to iNO inspiration during the first 24 h of iNO treatment. No response was defined as an increase in SpO2 < 5% or the inability to sustain saturation levels in the first 24 h of iNO treatment. For descriptive statistics, χ2 and t-test analysis were used to compare categorical and continuous variables between the two groups. To evaluate independent risk factors of non-responsiveness to iNO treatment, binary logistic regression analysis were performed.Results: A total of 75 newborns were included in the study. Sixty-two cases were in the responders group, and 13 cases were in the non-responders group. Univariate analysis showed that asphyxia, neonatal respiratory distress syndrome (NRDS), pulmonary surfactant administration, meconium aspiration syndrome (MAS), the severity of pulmonary hypertension (PH), and high-frequency oscillatory ventilation (HFOV) therapy were the high-risk factors affecting the response to iNO treatment in the newborns with PPHN. The binary logistic regression analysis indicated that asphyxia and NRDS incidence were independent predictors of non-responsiveness to iNO treatment [asphyxia: OR 4.193, 95% CI 1.104-15.927, P = 0.035; NRDS: OR 0.154, 95% CI 0.036-0.647, P = 0.011]. The patients in the non-responders group had shorter iNO inspiration followed by MV duration, supplemental oxygen and hospital stay, and higher mortality. There were no significant differences in IVH, PVL, and BPD between two groups.Conclusion: In the newborns with PPHN, asphyxia and NRDS resulted as the independent risk factors of non-responsiveness to iNO therapy. Asphyxia in the newborns with PPHN is detrimental to the response to iNO treatment, while NRDS is beneficial.